Whole-brain voxel-based analysis of diffusion tensor MRI parameters in patients with primary open angle glaucoma and correlation with clinical glaucoma stage - Dai, Hui (2012)
INTRODUCTION: Glaucoma is the second leading cause of blindness worldwide. The purpose of this study is to identify areas of neurodegeneration in glaucoma utilizing 3 T magnetic resonance (MR) diffusion tensor imaging (DTI) parameters with whole-brain voxel-based analysis (VBA) and determine whether these parameters correlate with disease severity. METHODS: Twenty-five glaucoma patients and 25 age-matched healthy volunteers were prospectively examined. Clinical glaucoma severity was assessed utilizing static threshold visual field parameters. All subjects underwent 3 T MRI utilizing a DTI sequence (repetition time/echo time 13,000/68.9 ms, maximal b value 800 s/mm(2) along 30 directions) and an anatomic sequence to provide structural information. All data sets were processed by VBA. Brain fractional anisotropy, mean diffusivity (MD), radial diffusivity (RD), and axial diffusivity (AD) were compared in the two groups. Correlation between DTI parameters and glaucoma stage were determined. RESULTS: The bilateral optic radiations and chiasma of glaucoma patients demonstrated statistically significantly lower fractional anisotropy (p<0.05). Optic radiation RD was similarly decreased in glaucoma patients (p<0.05). There were no statistically significant differences noted in MD or AD between the two groups (p>0.05). Optic chiasm fractional anisotropy values were negatively correlated with glaucoma stage (r=−0.53, p<0.05) and optic radiation RD values positively correlated (left r=0.45, p<0.05; right = 0.38, p=0.06). CONCLUSION: DTI parameters fractional anisotropy and RD are altered in the optic chiasm and radiations of glaucoma patients. As fractional anisotropy and RD also correlate with glaucoma stage, these values could serve as potential non-invasive markers of disease severity.